Combined impact of tropical central‐eastern Pacific and North Atlantic sea surface temperature on precipitation variation in monsoon transitional zone over China during August–September. (1st August 2019) - Zhao, Wei; Chen, Wen; Chen, Shangfeng; Yao, Shuai‐Lei; Nath, Debashis
Abstract: Previous studies suggested that sea surface temperature (SST) anomalies in the tropical central‐eastern Pacific (TCEP) and tropical Northern Atlantic (TNA) both have significant impacts on the inter‐annual variation of precipitation over the monsoon transitional zone (MTZ) in China during August–September. This study further reveals that the relationship between TCEP (TNA) SST and MTZ precipitation during August–September is strongly modulated by the sign of the TNA (TCEP) SST. When TCEP and TNA SST anomalies have the same sign, connections of the TCEP and TNA SST with the MTZ precipitation are unclear. In contrast, TCEP and TNA SST changes both have significant relation with the MTZ precipitation when they have the opposite sign. During the same‐sign years, the anticyclonic (cyclonic) anomaly over the western North Pacific generated by the TCEP SST cooling (warming) is weakened by the cyclonic (anticyclonic) anomaly triggered by the TNA SST cooling (warming). Thus, connections of the MTZ precipitation with the TCEP and TNA SST are weak. However, during the opposite‐sign years, the anticyclonic anomalies over the western North Pacific generated by the TCEP SST anomalies have a constructive superposition on those induced by the TNA SST changes. As such, connections of the TCEP and TNA SST with the MTZ precipitation variation are significant. Further analysis shows that the prediction skill of precipitation over the MTZ is enhanced if taking both the TCEP and TNA SST signals into account. Abstract : Relation between TCEP (TNA) SST and MTZ precipitation variation in August–September is strongly modulated by the sign of TNA (TCEP) SST. When TCEP and TNA SST anomalies have the same (opposite) sign, connections of TCEP and TNA SST with the MTZ precipitation are strong (weak). Prediction skill of the precipitation variations over the MTZ is enhanced if taking both the TCEP and TNA SST into account. In the figure, scatterplots of the August–September MTZ precipitation index versus simultaneous (a) Niño3.4 index and (b) TNA_res SST index plotted only for years in which the Niño3.4 index and TNA_res SST index are in‐phase. (b, d) Same as (a, c), but plotted for years in which the Niño3.4 index and TNA_res SST index are out‐of‐phase.